Agency and strategic contracts: theory and evidence from R&D agreements in the pharmaceutical industry - Guo, Di; Hua, Xinyu; Jiang, Kun (Elsevier, 2017)
We examine the use of strategic rights in research and development (R&D) agreements between a client and an agent, when an entrant may compete with the client for the license of non-contracted discoveries developed by the agent. The agent puts effort either in the contracted project, or into other R&D activities which can result in non-contracted discoveries. Strategic rights help the client and the agent extract rent from the entrant, and also motivate the agent to place effort into the contracted project. Accordingly, firms are more likely to adopt strategic rights when the likelihood of entry is larger. Moreover, strategic rights and termination rights are substitutes in mitigating agency problems. By investigating R&D agreements between pharmaceutical clients and bio-tech agents, we find consistent evidence of the positive impact of entry threat on the use of strategic rights, as well as evidence of the substitution between strategic rights and termination rights.